2021
DOI: 10.1016/j.ejim.2021.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing PaO2 for PaCO2 in P/F ratio predicts in-hospital mortality in acute respiratory failure due to Covid-19: A pilot prospective study

Abstract: Up to fifteen percent of patients with novel pandemic coronavirus disease have acute respiratory failure (ARF). Ratio between arterial partial pressure of oxygen (PaO2) and fraction of inspired oxygen (FiO2), P/F, is currently used as a marker of ARF severity in Covid-19. P/F does not reflect the respiratory efforts made by patients to maintain arterial blood oxygenation, such as tachypnea and hyperpnea, leading to hypocapnia. Standard PaO2, the value of PaO2 adjusted for arterial partial pressure of carbon d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Our data confirms preceding studies which showed that in patients with COVID-19 pneumonia low P/F, low SpO 2 /FiO 2 ratio, low PCO 2 and the presence of dyspnea at rest predict the need of NIRS [ 12 , 13 , 14 , 34 , 35 ]. Of note, there is a slight discrepancy between PaO 2 /FiO 2 and SpO 2 /FiO 2 cut off, which predicts NIRS requirement (respectively 280 and 438).…”
Section: Discussionsupporting
confidence: 92%
“…Our data confirms preceding studies which showed that in patients with COVID-19 pneumonia low P/F, low SpO 2 /FiO 2 ratio, low PCO 2 and the presence of dyspnea at rest predict the need of NIRS [ 12 , 13 , 14 , 34 , 35 ]. Of note, there is a slight discrepancy between PaO 2 /FiO 2 and SpO 2 /FiO 2 cut off, which predicts NIRS requirement (respectively 280 and 438).…”
Section: Discussionsupporting
confidence: 92%
“…A correction of PaO2 by arterial carbon dioxide tension (PaCO2) − namely, standardized PaO 2 − was suggested to overcome this latter limit [ 10 ]. The role of standard P/F ( ST P/F) ratio was recently found to be accurate and superior to P/F in predicting in-hospital mortality in coronavirus disease 2019 (COVID-19) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, we did not record PaCO 2 values during our two studies [2] , [4] ; however, previous literature showed that patients with severe COVID-19 have lower inspiratory effort in comparison to matched non-COVID-19 cohort with respiratory failure, suggesting lower risk of P-SILI in patients with COVID-19 [4] . Furthermore, data from COVID-19 patients showed that PaCO 2 was not significantly lower in patients who later needed mechanical ventilation, and that PaCO 2 showed low accuracy in predicting the need for mechanical ventilation and/or death with area under receiver operating characteristic (95% confidence interval) of 0.57 (0.51 to 0.68) [5] . Thus, we suggest that the level of PaCO 2 on hospital admission is unlikely a predictor of severity of the disease.…”
mentioning
confidence: 99%